LITERATURE LITERACY IN CHILD SPECIAL DEVELOPMENT INSTITUTIONS (LPKA) CLASS II MAROS, SOUTH SULAWESI - Inriati Lewa; Syahwan Alfianto Amir; AB. Takko Bandung; Nurhayati Nurhayati (LPPM Institut Pendidikan Nusantara Global, 2023)
This study aims to apply literary literacy at the Class II Child Special Development Institute (LPKA) Maros, South Sulawesi. This research method is descriptive qualitative with a field study approach (field study) through a deductive model to understand the research problem. The source of the data in this study was Andikpas (Correctal Students), totaling 28 men. The results of this study indicate that Andikpas is able to convey empirical experiences in the coaching process they experience at LPKA through literary literacy. They all have the same hopes, namely they want to be free soon so they can be with their parents (family) and friends, they want to be free so they can continue their education, and they want to be free so they can work to help support their family. Of these three things, Andikpas hopes most dominantly, so that he wants to be free soon, is to gather with his parents.